The efficient generation of knockout microglia cells using a dual-sgRNA strategy by CRISPR/Cas9 - Zhang, Mengfei; Yi, Fang; Wu, Junjiao; Tang, Yu (Frontiers in Molecular Neuroscience, 2022)
Gene deletion in microglia has become an important and exciting approach for studying neuroinflammation, especially after the development of the CRISPR/Cas9 system for genome editing during the last decade. In this study, we described a protocol for the high-efficient generation of knockout microglia cells using a dual-short guide RNA (sgRNA) strategy by CRISPR/Cas9. Leucine-rich repeat kinase 2 (LRRK2), as a pathogenic gene of Parkinson’s disease (PD), has played versatile roles during the disease development. Despite many key insights into LRRK2 studies, the normal and disease-related functions of LRRK2 in microglia and neuroinflammation remain to be fully investigated. Given the importance of LRRK2 in PD pathogenesis, we thus designed and applied the protocol to target LRRK2. Specifically, we designed two sgRNAs targeting the N terminus of LRRK2, spanning the 5’ untranslated region (UTR) and exon 1, and screened knockout cells by single cell expansion. In practice, the dual-sgRNA system can facilitate us to obtain knockout cells in a more convenient, rapid and accurate way. Candidate knockout cells can be easily distinguished by genomic PCR and running on agarose gels, based on the different band sizes. Successful knockouts were further verified by Sanger sequencing and Western blot. Using this protocol, we obtained a LRRK2-deficient microglia cell line, which was characterized by longer cellular processes, enhanced adhesion and weakened migration capacity. The knockout microglia may further serve as an important cellular tool to reveal conserved and novel aspects of LRRK2 functions in the development and progression of PD. Our protocol using dual-sgRNA targeting guarantees >60% targeting efficiency, and could also be applied to targeting other genes/loci, especially non-coding RNAs and regulatory elements.